على الحمل البكتيري للحم الدجاج الطري Ianthus carphyllus تاثير مستخلصات ثمار نبات القرنفل - جعفر محمد موسى; كريدي حسين عوده; مطلك خميس حبيب; احمد سندس حميد (Al-Nahrain Journal of Science, 2018)
The Study was carried out to isolation and identification of Salmonella. typhimurium Staphylococcus. aureus, Listeria monocytogenic, Pseudomonas aeruginosa which consider the most important causes of fresh meat contamination, the extraction of active substances of clove fruits was extract by using alcoholic Extraction (cold and hot) and water extraction (cold and hot), the effects of the active constituents were studied to appear their activity to Reduce the growth of the bacterial isolates by using o.3% concentration and minimum inhibition concentration method (MIC). The results indicate that the hot alcoholic extraction o.3% was the best extraction in reducing the growth of bacteria by measuring the inhibition zone diameter